Molecular Marker Linked to Number of Female Flowers per Node in Cucumber. Issue 4 (3rd July 2016) - Khasmakhi-Sabet, S. A.; Abdousi, V.; Samizadeh, H.; Kalatejari, S.
ABSTRACT: Quantitative traits, including yield, are difficult to study due to the complex nature of their inheritance. Single marker analysis is the simplest method for detecting quantitative trait loci associated with single markers and does not require a complete linkage map. This method determines associations between marker genotypes and trait value. A project was undertaken to identify suitable markers linked with number of female flowers per node in cucumber ( Cucumis sativus L.) using single marker analysis for use in selection early in plant development. A marker with a positive correlation with number of female flowers can be used for marker-assisted selection to increase the number of female flowers per node in cucumber, which is positively correlated with yield. One of the polymorph alleles of parents UBC813, UBC815, UBC876 intersimple sequences repeat (ISSR) markers and UBC811+TOS2 and UBC812+TOS2 hybrids had significant linkage with number of female flowers per node in the F2 population. These genes are close together and are associated with a linkage. The genes are likely located on the same chromosome and enter into gametes together to be incorporated.